Growth and Convergence across the United States: Evidence from County-Level Data - Matthew J. Higgins; Daniel Levy; Andrew T. Young (Review of Economics and Statistics, 2006)
We use U.S. county data (3,058 observations) and 41 conditioning variables to study growth and convergence. Using ordinary least squares (OLS) and three-stage least squares with instrumental variables (3SLS-IV), we report on the full sample and metro, nonmetro, and and regional samples: (1) OLS yields convergence rates around 2%; 3SLS yields 6%–8%; (2) convergence rates vary (for example, the Southern rate is 2.5 times the Northeastern rate); (3) federal, state, and local government negatively correlates with growth; (4) the relationship between educational attainment and growth is nonlinear; and (5) the finance, insurance, and real estate industry and the entertainment industry correlate positively with growth, whereas education employment correlates negatively.
Keywords: O40; O11; O18; O51; R11; H50; H70; 330; Economic Growth; Conditional Convergence; and County-Level Data